Pemanfaatan Kawasan Mangrove Lantebung Sebagai Laboratorium Alam Berbasis Field Work Pada Mata Pelajaran Geografi - Musyawarah, Rahma (Journal of Geographical Sciences and Education, 2024)
Natural laboratories are ideal locations for fieldwork activities as they provide authentic learning resources, enabling students to study natural processes, ecosystem dynamics, and human-environment interactions directly. The aim of this study is to examine the potential of the Lantebung mangrove area as a natural laboratory for geography learning. This research is classified as qualitative descriptive research. The results of the study show: 1) The Lantebung mangrove area has potential as a study object for geography learning based on fieldwork, including biodiversity and local community activities related to resource management and utilization; 2) the stages of fieldwork-based learning include planning, preparation of materials and logistics, activity briefing, field observation, data collection, discussion and analysis, as well as presentation and reflection; and 3) challenges in implementing fieldwork-based learning include location, diverse initial understanding of students, ecosystem disturbances, time, budget and logistics, coordination with local communities, as well as safety and health.